DEFEND ID as an Instrument of Indonesian Defense Diplomacy: A Case Study of Industrial Cooperation and Capacity Building in Indonesia-France Relations - Sekar Hesti Suminar; Frega Wenas Inkiriwang; Anak Agung Banyu Perwita (Darul Yasin Al Sys, 2026)
This study analyzes the function of DEFEND ID as an instrument of Indonesian defense diplomacy through a case study of defense industrial cooperation between Indonesia and France. Against the backdrop of Indonesia’s defense modernization agenda and the increasingly complex strategic environment in the Indo-Pacific, this study examines how DEFEND ID operates as a state-owned defense industry holding and a strategic platform for advancing the national defense agenda. Drawing on the theoretical perspectives of neorealism, defense diplomacy, and capacity building, the study explores the relationship between defense industrial cooperation and the enhancement of national defense capabilities. The findings show that collaboration between DEFEND ID entities and major French defense companies has moved beyond conventional defense procurement to include broader industrial partnerships, technology transfer, technical training, and knowledge sharing. These mechanisms position DEFEND ID as a bridge between Indonesia’s foreign policy objectives and the development of its domestic defense industry. From a neorealist perspective, this cooperation reflects Indonesia’s effort to strengthen national capabilities and reduce strategic dependence in an increasingly competitive security environment. Defense diplomacy functions as a channel for translating strategic partnerships into concrete outcomes, while capacity building emerges through technological development, human resource strengthening, and industrial enhancement. This study concludes that DEFEND ID plays a critical role in connecting international defense cooperation with Indonesia’s long-term objectives of defense modernization, strategic autonomy, and defense industrial self-reliance.